TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen characteristics and preparation method thereof

CN122897366APending Publication Date: 2026-10-13CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611089484.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

该技术方案同样存在负价氢问题

Benefits of technology

[0033]1、工艺简单,反应条件温和,具体体现为,通过化学还原法形成氧缺陷TiO2,缺陷表面吸附的H+/H−可形成独特的双极氢结构,通过表面H+/H−的静电作用有效诱导MgH2表面释放H−。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897366A_ABST
    Figure CN122897366A_ABST
Patent Text Reader

Abstract

This invention discloses a TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties, prepared by ball milling TiO2-D and MgH2, wherein MgH2 is the matrix material and TiO2-D is the catalyst; the TiO2-D is prepared by chemical reduction, and both TiO2 and TiO2-D have anatase structures; the content of positively valence hydrogen in the bipolar hydrogen of TiO2-D ranges from 0 to 0.35, and the content of negatively valence hydrogen ranges from 0 to 0.23. The preparation method includes the following steps: 1. Preparation of TiO2 precursor; 2. Preparation of oxygen-deficient TiO2-D; 3. Preparation of MgH2 / TiO2-D. At a hydrogen release temperature of 300℃ and a hydrogen release pressure of 0.001 MPa, the hydrogen release amount of MgH2 / TiO2-D reaches 6.20–6.41 wt.% after a hydrogen release time of 7 min; at a hydrogen release temperature of 280℃ and a hydrogen release pressure of 0.001 MPa, the hydrogen release amount of MgH2 / TiO2-D reaches 5.81–5.98 wt.% after a hydrogen release time of 15 min; the activation energy of MgH2 / TiO2-D is 92–116 kJ / mol. ‑1 Under vacuum conditions, the heating rate is 2℃ / min. ‑1 When the temperature rises from room temperature to 450℃, the initial hydrogen release temperature of MgH2 / TiO2-D is 201.3-205.8℃, the complete hydrogen release temperature is 345-350℃, and the total hydrogen release amount is 6.52-6.64 wt.%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hydrogen storage materials technology, specifically relating to a TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties and its preparation method. Background Technology

[0002] Hydrogen energy boasts advantages such as wide availability, clean and carbon-free operation, flexibility, and high efficiency, with an energy density approximately three times that of gasoline. Among hydrogen storage materials, magnesium-based hydrogen storage material MgH2 combines high hydrogen storage density, good reversibility, and abundant resources. However, MgH2 suffers from a very high surface hydrogen atom dissociation barrier. The initial dehydrogenation barrier of MgH2 is as high as 2.53 eV. This fundamental property makes it difficult for surface hydrogen to dissociate, leading to high hydrogen absorption and desorption temperatures and slow reaction kinetics in magnesium-based hydrogen storage materials.

[0003] Adding a catalyst can significantly reduce the hydrogen adsorption and desorption temperatures of MgH2 and improve the reaction kinetic rate. For example, existing literature 1 ("Catalytic effect of transition metals on hydrogen sorption in nanocrystalline ball milled MgH2-Tm (Tm=Ti, V, Mn, Fe and Ni) systems" Journal of Alloys and Compounds, 1999, 292(1-2): 247-252.) found that the Ti-containing composite material exhibited faster kinetic performance after MgH2 was combined with 3d transition metals Ti, V, Mn, Fe, and Ni through high-energy ball milling. However, although such transition metals based on Ti can effectively adsorb and dissociate hydrogen, the Ti-H bond energy is relatively large, leading to a decrease in the subsequent diffusion rate, ultimately resulting in a relatively low improvement in the kinetic performance of MgH2.

[0004] Similar to Ti-based catalysts, existing literature 2 (“Particle size effect of TiO2 on the catalysis of MgH2”, International Journal of Hydrogen Energy, 2026, 212:153633.) describes how TiO2 is doped into MgH2 through ball milling, achieving a technical effect that reduces the initial hydrogen desorption temperature to 234.2℃.

[0005] To address the issue of decreased subsequent diffusion rates in Ti-based catalysts, oxygen vacancies can be created in the crystal lattice to weaken Mg-H bonds and accelerate dehydrogenation. For example, existing literature 3 (《Engineering the OxygenVacancies in Na2Ti3O7 for Boosting Its Catalytic Performance in MgH2 HydrogenStorage》ACS Sustainable Chemistry & Engineering, 2021, 10(1): 363-371.) first applied oxygen vacancy engineering to Na2Ti3O7 catalysts, achieving a reduction in the initial dehydrogenation temperature from 287℃ to 183℃ by creating oxygen vacancies in the crystal lattice. This technique uses oxygen vacancies as active centers to weaken Mg-H bonds. However, since Ti in Na2Ti3O7 can form Ti-H bonds, and H is negatively charged hydrogen, the same as H in MgH2, there is a repulsive effect between hydrogens of the same polarity, thus hindering the hydrogen storage performance of MgH2. This technical problem is simply referred to as the negatively charged hydrogen problem.

[0006] Similar Ti-based catalysts include existing literature 4 (《Nanoconfined and in Situ Catalyzed MgH2 Self-Assembled on 3D Ti3C2 MXene Folded Nanosheets with Enhanced Hydrogen Sorption Performances》ACS Nano, 2021; 15 (11):18494.), which synthesizes Ti3C2 folded nanosheets as a supporting material with loading capacity to improve the hydrogen storage performance of MgH2 nanoparticles. This technical approach also suffers from the problem of negatively valent hydrogen. Summary of the Invention

[0007] The purpose of this invention is to provide a TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties and its preparation method. The basic technical principle is to utilize the H adsorbed on the defect surface of TiO2... + / H − And then through surface H + / H − Electrostatic interaction induces the release of H from the MgH2 surface − This solves the problem in existing technologies where hydrogens of the same polarity repel each other, i.e., the problem of negatively valent hydrogen.

[0008] To achieve the above objectives, the present invention adopts the following technical solution:

[0009] A TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties is prepared by ball milling TiO2-D and MgH2, wherein MgH2 is the matrix material and TiO2-D is the catalyst; the TiO2-D is prepared by chemical reduction, and both TiO2 and TiO2-D have anatase structure; in the TiO2-D, the content of positively valence hydrogen in the bipolar hydrogen ranges from 0 to 0.35, and the content of negatively valence hydrogen ranges from 0 to 0.23.

[0010] A method for preparing a TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties includes the following steps:

[0011] Step 1, Preparation of TiO2 precursor: First, at room temperature, tetrabutyl titanate, concentrated hydrochloric acid and anhydrous ethanol are stirred and thoroughly dissolved to obtain a uniform and transparent sol. Then, the sol is dried. Finally, the sol is calcined in air at a certain temperature to obtain TiO2 precursor.

[0012] In step 1, the mixing ratio of tetrabutyl titanate, concentrated hydrochloric acid and anhydrous ethanol is 72:2:15, and the stirring time is 12-24 h.

[0013] In step 1, the drying temperature is 60-80℃ and the drying time is 12-24 h;

[0014] In step 1, the calcination temperature is 450℃ and the calcination time is 2 h.

[0015] Step 2, preparation of TiO2 with bipolar hydrogen characteristics: First, under an argon atmosphere, the TiO2 precursor obtained in Step 1 is ball-milled and mixed with NaBH4 reducing agent. Then, it is heat-treated. Finally, the heat-treated solid powder is placed in hydrochloric acid solution and magnetically stirred. After stirring, it is washed, centrifuged and vacuum dried to obtain TiO2 with bipolar hydrogen characteristics, abbreviated as TiO2-D.

[0016] In step 2, the mass ratio of TiO2 precursor to NaBH4 is 2:1;

[0017] In step 2, the ball milling conditions are as follows: under argon gas, the ball-to-material ratio is 20:1, the ball milling speed is 150 rpm, and the ball milling method is intermittent ball milling, specifically, the ball milling time is 10 min, the pause time is 10 min, and then the ball milling is reversed, with a total ball milling time of 2 h.

[0018] In step 2, the heat treatment conditions are as follows: under argon atmosphere, the gas flow rate is 150 mL / min. -1 The heat treatment temperature was 450℃ and the heat treatment time was 2 hours.

[0019] In step 2, the concentration of hydrochloric acid is 1 mol L. -1 The amount of hydrochloric acid is 100 mL, and the stirring conditions are: stirring speed of 600-800 rpm and stirring time of 12-24 h.

[0020] Step 3, Preparation of MgH2 / TiO2-D: Under an argon atmosphere, MgH2 and TiO2-D obtained in Step 2 are ball-milled to obtain a TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties, referred to as MgH2 / TiO2-D.

[0021] In step 3, the mass ratio of MgH2 to TiO2-D obtained in step 2 is 9:1;

[0022] In step 3, the ball milling conditions are as follows: under argon gas, the ball-to-material ratio is 20:1, the ball milling speed is 300 rpm, and the ball milling method is intermittent ball milling, specifically, the ball milling time is 10 min, the pause time is 10 min, and then the ball milling is reversed, with a total ball milling time of 20 h.

[0023] A TiO2-magnesium-based composite hydrogen storage material with bipolar hydrogen properties exhibits the following characteristics: hydrogen release temperature at 300℃ and hydrogen release pressure at 0.001 MPa; hydrogen release amount of MgH2 / TiO2-D reaches 6.20-6.41 wt.% after 7 min of hydrogen release time; hydrogen release temperature at 280℃ and hydrogen release pressure at 0.001 MPa; hydrogen release amount of MgH2 / TiO2-D reaches 5.81-5.98 wt.% after 15 min of hydrogen release time; and the activation energy of MgH2 / TiO2-D is 92-116 kJ / mol. -1 Under vacuum conditions, the heating rate is 2℃ / min. -1 When the temperature rises from room temperature to 450℃, the initial hydrogen release temperature of MgH2 / TiO2-D is 201.3-205.8℃, the complete hydrogen release temperature is 345-350℃, and the complete hydrogen release amount is 6.52-6.64 wt.%.

[0024] The technical effects of this invention have been tested and confirmed to be:

[0025] XRD analysis showed that TiO2 was pure anatase TiO2; after NaBH4 reduction and acid washing, TiO2-D was anatase TiO2; and the NaBH4 reduction treatment had no substantial effect on the phase composition of TiO2-D.

[0026] EPR testing revealed that TiO2-D exhibited defective structures after NaBH4 reduction treatment.

[0027] TG analysis revealed that the mass of TiO2-D exhibited a trend of first decreasing and then increasing. The decrease in mass was due to the removal of adsorbed and weakly bound water from the surface and pores of TiO2-D. The increase in mass was due to the reaction of oxygen vacancies in TiO2-D with oxygen from the air, resulting in oxygen absorption. When the mass no longer changed, it indicated that TiO2-D had reverted to pure TiO2. TG test results showed that the specific O content was 1.57%, therefore, the chemical formula is TiO2. 1.57 .

[0028] The isothermal hydrogen absorption test showed that TiO2-D absorbed 0.68 wt.%, which is the content of bipolar hydrogen in TiO2-D. The calculated content of bipolar hydrogen is 0.50%.

[0029] NMR analysis revealed chemical signals in TiO2-D at chemical shifts of -0.73 and -4.36 ppm, corresponding to H2O, respectively. + and H − And, H + and H − The ratio is 7:3. Combined with the results of the isothermal hydrogen absorption test, it can be seen that in the bipolar hydrogen, the value of positively charged hydrogen is 0.35, and the value of negatively charged hydrogen is 0.15. Therefore, the specific chemical formula of TiO2-D is TiO2. 1.57 (H + ) 0.35 (H − ) 0.15 .

[0030] The hydrogen desorption kinetics tests showed that at a hydrogen desorption temperature of 300℃, a hydrogen desorption pressure of 0.001 MPa, and a hydrogen desorption time of 7 min, the hydrogen desorption capacity of MgH2 / TiO2-D reached 6.20-6.41 wt.%; at a hydrogen desorption temperature of 280℃, a hydrogen desorption pressure of 0.001 MPa, and a hydrogen desorption time of 15 min, the hydrogen desorption capacity of MgH2 / TiO2-D reached 5.81-5.98 wt.%; the calculated activation energy of MgH2 / TiO2-D was 92-116 kJ / mol. -1 .

[0031] Performance testing of the hydrogen-degrading TPD under programmed temperature rise showed that, under vacuum conditions, the heating rate was 2℃ / min. -1 When the temperature rises from room temperature to 450℃, the initial hydrogen release temperature of MgH2 / TiO2-D is 201.3-205.8℃, the complete hydrogen release temperature is 345-350℃, and the complete hydrogen release amount is 6.52-6.64 wt.%.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] 1. The process is simple and the reaction conditions are mild. Specifically, oxygen-deficient TiO2 is formed through chemical reduction, and H2 adsorbed on the defect surface... + / H − It can form a unique bipolar hydrogen structure, through surface H + / H − The electrostatic effect effectively induces the release of H from the MgH2 surface. − .

[0034] 2. Furthermore, compared with the prior art, the present invention has superior hydrogen storage kinetic performance. At the same hydrogen release temperature, compared with Comparative Example 1, the hydrogen release time is shortened by 53.4%, the activation energy is reduced by 26.8%, and the initial hydrogen release temperature is lower (203.5℃), which is 17.7% lower than that of Comparative Example 1.

[0035] 3. Furthermore, the raw material costs are low and the environment is environmentally friendly. Specifically, the raw materials tetrabutyl titanate and sodium borohydride are commercial pharmaceuticals with wide availability and low prices. Attached Figure Description

[0036] Figure 1 The XRD pattern of TiO2 in Example 1; Figure 2 The XRD pattern of TiO2-D in Example 1; Figure 3 The EPR spectrum of TiO2-D in Example 1; Figure 4 The TG spectrum of TiO2-D in Example 1; Figure 5 The isothermal hydrogen absorption curve of TiO2-D in Example 1; Figure 6 The NMR spectrum of TiO2-D in Example 1; Figure 7 The isothermal hydrogen desorption curves of MgH2, Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3 at 300°C are shown. Figure 8 The isothermal hydrogen desorption curves of MgH2, Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3 at 280°C are shown. Figure 9 TPD curves of hydrogen desorption in MgH2, Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3 at temperature-programmed elevation; Figure 10 The activation energy calculation diagrams are for MgH2, Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3. Detailed Implementation

[0037] The present invention will be further described in detail through embodiments and with reference to the accompanying drawings, but this is not intended to limit the scope of the invention.

[0038] Example 1

[0039] A method for preparing a TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties includes the following steps:

[0040] Step 1, Preparation of TiO2 precursor: First, at room temperature, tetrabutyl titanate, concentrated hydrochloric acid and anhydrous ethanol are stirred for 12 hours to fully dissolve and mix evenly to obtain a uniform and transparent sol. Then, the sol is dried at 80°C for 12 hours. Finally, the sol is calcined in air at 450°C for 2 hours to obtain the TiO2 precursor.

[0041] To determine the phase composition of the TiO2 precursor, XRD analysis was performed. The test results are as follows: Figure 1 As shown, the TiO2 precursor contains characteristic peaks of TiO2 with anatase structure.

[0042] Step 2, Preparation of TiO2 with Bipolar Hydrogen Properties: First, ball milling was performed at an argon gas pressure of 0.2 MPa, a ball-to-material ratio of 20:1, a ball milling speed of 150 rpm, and an intermittent ball milling method for 2 h. The TiO2 precursor obtained in Step 1 was then ball-milled with NaBH4 reducing agent at a mass ratio of 2:1. Then, under argon gas conditions, the gas flow rate was 150 mL / min. -1 The solid powder was heat-treated at 450℃ for 2 hours. Finally, it was magnetically stirred for 12 hours and then placed in hydrochloric acid solution for magnetic stirring. After stirring, it was washed, centrifuged and vacuum dried to obtain TiO2 with bipolar hydrogen characteristics, abbreviated as TiO2-D.

[0043] In step 2, the intermittent ball milling conditions are as follows: the ball milling time is 10 min, the pause time is 10 min, and then the ball milling is reversed, with a total ball milling time of 2 h.

[0044] To determine the phase composition of TiO2-D, XRD analysis was performed. The test results are as follows: Figure 2 As shown, TiO2-D also contains characteristic peaks of TiO2 with anatase structure. Comparison with step 1 shows that the NaBH4 reduction treatment in step 2 has no substantial impact on the phase composition of TiO2-D.

[0045] To demonstrate the presence of oxygen vacancies in TiO2-D, an EPR test was performed. The test results are as follows: Figure 3As shown, TiO2-D exhibits a distinct diffraction peak at g=2.003, indicating the presence of oxygen vacancies. The test results demonstrate that TiO2-D possesses a defect structure.

[0046] To further quantify the defect content of TiO2-D, i.e., oxygen vacancies, TG testing was performed under air conditions. The test results are as follows: Figure 4 As shown, during the heating process, the mass change trend of TiO2-D shows a characteristic of first decreasing and then increasing;

[0047] The reason for the quality decline is the removal of adsorbed water and weakly bound water on the surface and in the pores of TiO2-D;

[0048] The reason for the quality improvement is that oxygen vacancies in TiO2-D react with oxygen in the air and absorb oxygen.

[0049] When the mass no longer changes, it indicates that TiO2-D has been transformed back into pure TiO2.

[0050] Test results show that TiO2-D has an oxygen absorption capacity of 9.4%. Calculations indicate that the specific O content is 1.57%, therefore, its chemical formula is TiO2-D. 1.57 .

[0051] To further quantify the bipolar hydrogen content in TiO2-D, isothermal hydrogen absorption testing was conducted. The specific conditions for isothermal hydrogen absorption were: absorption temperature of 300℃, hydrogen pressure of 40 bar, and absorption time of 2 hours. The test results are as follows: Figure 5 As shown, the hydrogen absorption capacity of TiO2-D is 0.68 wt.%, and the specific hydrogen content of the bipolar electrode is calculated to be 0.50%.

[0052] To further prove the H in bipolar hydrogen + and H − The proportion was used for NMR testing. The test results are as follows: Figure 6 As shown, H + and H − The ratio is 7:3. Based on the results of the isothermal hydrogen absorption test, it can be calculated that in the bipolar hydrogen, the value of positively valence hydrogen is 0.35, and the value of negatively valence hydrogen is 0.15. Therefore, the chemical formula is further determined to be TiO₂. 1.57 (H + ) 0.35 (H − ) 0.15 .

[0053] Step 3, Preparation of MgH2 / TiO2-D: Argon gas pressure is 0.2 MPa, ball-to-material ratio is 20:1, ball milling speed is 300 rpm, ball milling time is 10 h, and the mass ratio of MgH2 to TiO2-D obtained in step 2 is 9:1. MgH2 and TiO2-D are intermittently ball milled to obtain a TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties, abbreviated as MgH2 / TiO2-D.

[0054] In step 3, the intermittent ball milling conditions are as follows: the ball milling time is 10 min, the pause time is 10 min, and then the ball milling is reversed, with a total ball milling time of 20 h.

[0055] To demonstrate the hydrogen storage performance of MgH2 / TiO2-D, kinetic performance tests were conducted. Simultaneously, to demonstrate the role of TiO2-D, pure MgH2 was ball-milled and its kinetic performance was tested. The conditions for the kinetic performance tests were: hydrogen release pressure of 0.001 MPa, and hydrogen release temperatures of 280℃ and 300℃, respectively.

[0056] The test results at a hydrogen release temperature of 300℃ are as follows: Figure 7 As shown, the hydrogen release amount of pure MgH2 was 0.02 wt.% at a hydrogen release time of 15 min and 0.79 wt.% at a hydrogen release time of 60 min; the hydrogen release amount of MgH2 / TiO2-D reached 6.41 wt.% at a hydrogen release time of 7 min.

[0057] The test results at a hydrogen release temperature of 280℃ are as follows: Figure 8 As shown, the hydrogen release amount of pure MgH2 at a hydrogen release time of 15 min is 0.02 wt.%; the hydrogen release amount at a hydrogen release time of 60 min is 0.79 wt.%; and the hydrogen release amount of MgH2 / TiO2-D at a hydrogen release time of 15 min reaches 5.98 wt.%.

[0058] Furthermore, the activation energy calculation results are as follows: Figure 10 As shown, the activation energy of pure MgH2 is 154.6 kJ / mol. -1 The activation energy of MgH2 / TiO2-D is 92.5 kJ / mol. -1 ;

[0059] The comparison shows that adding TiO2-D as a catalyst can significantly reduce the hydrogen desorption activation energy of MgH2.

[0060] To further demonstrate the hydrogen storage performance of MgH2 / TiO2-D, a temperature-programmed hydrogen desorption performance test was conducted. Simultaneously, to demonstrate the role of TiO2-D, pure MgH2 was ball-milled, and its temperature-programmed hydrogen desorption performance was tested. The test conditions were: under vacuum, a heating rate of 2℃ / min.-1 The temperature was increased from room temperature to 450℃. The test results are as follows: Figure 9 As shown,

[0061] The initial hydrogen release temperature of pure MgH2 is 327℃, the complete hydrogen release temperature is 450℃, the complete hydrogen release amount is 7.21 wt.%, and the hydrogen release rate is 94.7%.

[0062] The initial hydrogen release temperature of MgH2 / TiO2-D is 203.5℃, the complete hydrogen release temperature is 350℃, the complete hydrogen release amount is 6.64 wt.%, and the hydrogen release rate is 97.1%.

[0063] The comparison shows that adding TiO2-D catalyst can significantly reduce the initial hydrogen desorption temperature of MgH2, and TiO2-D catalyst can increase the hydrogen desorption rate of MgH2.

[0064] To demonstrate the impact of oxygen defects on hydrogen storage performance, Comparative Example 1 is provided, which describes a method for preparing an oxygen-defect-free TiO2 magnesium-based composite hydrogen storage material.

[0065] Comparative Example 1

[0066] A method for preparing a magnesium-based composite hydrogen storage material based on oxygen-free defect TiO2 is provided. The steps unless otherwise specified are the same as those in Example 1. The difference is that step 2 is not required. The TiO2 precursor obtained in step 1 is directly subjected to step 3. The resulting material is named MgH2 / TiO2.

[0067] To demonstrate the hydrogen storage performance of MgH2 / TiO2, kinetic performance tests were conducted.

[0068] The test results at a hydrogen release temperature of 300℃ are as follows: Figure 7 As shown, the hydrogen release rate of MgH2 / TiO2 at a hydrogen release time of 15 min is 6.25 wt.%;

[0069] The test results at a hydrogen release temperature of 280℃ are as follows: Figure 8 As shown, the hydrogen release amount of MgH2 / TiO2 was 2.61 wt.% when the hydrogen release time was 15 min, and 6.17 wt.% when the hydrogen release time was 60 min.

[0070] Furthermore, the activation energy calculation results are as follows: Figure 10 As shown, the activation energy of MgH2 / TiO2 is 126.3 kJ / mol. -1 Compared with Example 1, it can be seen that oxygen vacancies can significantly reduce the hydrogen desorption activation energy of MgH2.

[0071] To further demonstrate the impact of oxygen vacancies on hydrogen storage performance, a temperature-programmed hydrogen release performance test was conducted. The test results are as follows: Figure 9As shown, the initial hydrogen release temperature of MgH2 / TiO2 is 247.3℃, the complete hydrogen release temperature is 385℃, the complete hydrogen release amount is 6.81wt.%, and the hydrogen release rate is 99.5%.

[0072] Compared with Example 1, it can be seen that introducing oxygen vacancies can significantly reduce the initial hydrogen release temperature and the complete hydrogen release temperature of MgH2.

[0073] To further demonstrate the influence of bipolar hydrogen on hydrogen storage performance, Comparative Example 2 is provided, which is a method for preparing a TiH2 magnesium-based composite hydrogen storage material containing only negatively charged hydrogen. This method is compared with Example 1 to demonstrate the role of positively charged hydrogen. Meanwhile, Comparative Example 3 is provided, which is a method for preparing a pure Ti magnesium-based composite hydrogen storage material without bipolar hydrogen. This method is compared with Comparative Example 2 to demonstrate the role of negatively charged hydrogen.

[0074] Comparative Example 2

[0075] A method for preparing a magnesium-based composite hydrogen storage material containing only negatively charged hydrogen TiH2. Unless otherwise specified, the steps are the same as in Example 1. The difference is that steps 1 and 2 are not required. Commercially pure Ti powder is used as raw material and hydrogenated under certain conditions to obtain TiH2 containing only negatively charged hydrogen, which replaces TiO2-D in step 3. The resulting material is named MgH2 / TiH2.

[0076] The hydrogenation process is carried out at a temperature of 300°C, a pressure of 40 bar, and a time of 2 hours.

[0077] To demonstrate the hydrogen storage performance of MgH2 / TiH2, kinetic performance tests were conducted.

[0078] The test results at a hydrogen release temperature of 300℃ are as follows: Figure 7 As shown, the hydrogen release amount of MgH2 / TiH2 was only 1.76 wt.% when the hydrogen release time was 15 min, and 5.66 wt.% when the hydrogen release time was 60 min.

[0079] The test results at a hydrogen release temperature of 280℃ are as follows: Figure 8 As shown, the hydrogen release amount of MgH2 / TiH2 was 0.42 wt.% at a hydrogen release time of 15 min; and 1.87 wt.% at a hydrogen release time of 60 min.

[0080] Furthermore, the activation energy calculation results are as follows: Figure 10 As shown, the activation energy of MgH2 / TiH2 is 131.8 kJ / mol. -1 Compared with Example 1, positive valence hydrogen can significantly reduce the hydrogen desorption activation energy of MgH2, with a reduction of up to 29.8%.

[0081] To further demonstrate the impact of positively valent hydrogen on hydrogen storage performance, a temperature-programmed hydrogen release performance test was conducted. The test results are as follows: Figure 9 As shown, the initial hydrogen release temperature of MgH2 / TiH2 is 270.9℃, the complete hydrogen release temperature is 400℃, the complete hydrogen release amount is 6.54wt.%, and the hydrogen release rate is 95.6%.

[0082] Compared with Example 1, it can be seen that introducing positively charged hydrogen to form a bipolar hydrogen structure, utilizing H + With H in MgH2 − The electrostatic attraction between them weakens the Mg-H bond, thereby promoting the dissociation and diffusion of hydrogen atoms on the MgH2 surface, ultimately achieving a significant reduction in the initial hydrogen release temperature and the complete hydrogen release temperature of MgH2, and improving the hydrogen release rate.

[0083] Comparative Example 3

[0084] A method for preparing a pure Ti magnesium-based composite hydrogen storage material without bipolar hydrogen. The steps not specifically described are the same as in Example 1, except that steps 1 and 2 are not required. Commercial pure Ti powder is used as raw material to replace TiO2-D in step 3. The resulting material is named MgH2 / Ti.

[0085] To demonstrate the hydrogen storage performance of MgH2 / Ti, kinetic performance tests were conducted.

[0086] The test results at a hydrogen release temperature of 300℃ are as follows: Figure 7 As shown, the hydrogen release amount of MgH2 / Ti at a hydrogen release time of 15 min was only 0.31 wt.%; while the hydrogen release amount at a hydrogen release time of 60 min was 2.51 wt.%.

[0087] The test results at a hydrogen release temperature of 280℃ are as follows: Figure 8 As shown, the hydrogen release amount of MgH2 / Ti is 0.06 wt.% when the hydrogen release time is 15 min; and the hydrogen release amount is 0.33 wt.% when the hydrogen release time is 60 min.

[0088] Furthermore, the activation energy calculation results are as follows: Figure 10 As shown, the activation energy of MgH2 / Ti is 151.4 kJ / mol. -1 ;

[0089] Compared with Comparative Example 2, it can be seen that although introducing negatively valent hydrogen alone can also reduce the hydrogen desorption activation energy of MgH2, the reduction is only 13.0%.

[0090] To further demonstrate the impact of negatively valent hydrogen on hydrogen storage performance, a temperature-programmed hydrogen release performance test was conducted. The test results are as follows: Figure 9As shown, the initial hydrogen release temperature of MgH2 / Ti is 290.9℃, the complete hydrogen release temperature is 430℃, the complete hydrogen release amount is 6.55wt.%, and the hydrogen release rate is 95.8%.

[0091] Compared with Comparative Example 2, it can be seen that the introduction of negatively charged hydrogen can form Ti‒H bonds with Ti, promote the adsorption and dissociation of hydrogen, and reduce the initial hydrogen release temperature and the complete hydrogen release temperature of MgH2.

[0092] To demonstrate the impact of defect level and bipolar hydrogen ratio on hydrogen storage performance, Examples 2 and 3 are provided, namely TiO2 magnesium-based composite hydrogen storage materials with low oxygen defect structure and low bipolar hydrogen and high oxygen defect structure and high bipolar hydrogen.

[0093] Example 2

[0094] A method for preparing a magnesium-based composite hydrogen storage material based on a low-oxygen defect structure and low-bipolar hydrogen TiO2 is disclosed. Unless otherwise specified, the steps are the same as in Example 1, except that in step 2, the amount of NaBH4 reducing agent is reduced to decrease the oxygen defect content. Specifically, the mass ratio of TiO2 precursor to NaBH4 reducing agent is 4:1. The low-oxygen defect content and low-bipolar hydrogen TiO2 obtained in step 2 is abbreviated as TiO2-DL. Furthermore, the magnesium-based composite hydrogen storage material based on a low-oxygen defect structure and low-bipolar hydrogen TiO2 obtained in step 3 is abbreviated as MgH2 / TiO2-DL.

[0095] To quantitatively analyze the defect content, i.e., oxygen vacancies, of TiO2-DL, TG testing was conducted under air conditions. The test results showed that the oxygen absorption of TiO2-DL was 0.43%. Calculations indicated that the specific O content was 1.97%, therefore, the chemical formula is represented as TiO2-DL. 1.97 -DL.

[0096] To further study TiO 1.5 In TiO₂, the content of bipolar hydrogen was quantitatively analyzed by isothermal hydrogen absorption testing. 1.57 -DL has a hydrogen absorption capacity of 0.19 wt.%, from which the specific content of bipolar hydrogen can be obtained, and the specific value of bipolar hydrogen is 0.14.

[0097] To further prove the H in bipolar hydrogen + and H − The ratio was used for NMR testing, H + and H − The ratio is 9:1. Based on the results of the isothermal hydrogen absorption test, the value of positively charged hydrogen in the bipolar hydrogen is 0.13, and the value of negatively charged hydrogen is 0.01. Therefore, the chemical formula is represented as TiO₂. 1.97 (H + ) 0.13 (H− ) 0.01 .

[0098] The above tests show that Example 2 successfully prepared TiO2 with low oxygen vacancy and low bipolar hydrogen.

[0099] To demonstrate the hydrogen storage performance of MgH2 / TiO2-DL, kinetic performance tests were conducted.

[0100] The test results at a hydrogen release temperature of 300℃ are as follows: Figure 7 As shown, the hydrogen release rate of MgH2 / TiO2-DL at a hydrogen release time of 15 min is 6.23 wt.%;

[0101] The test results at a hydrogen release temperature of 280℃ are as follows: Figure 8 As shown, the hydrogen release amount of MgH2 / TiO2-DL was 4.11 wt.% at a hydrogen release time of 15 min and 6.09 wt.% at a hydrogen release time of 30 min.

[0102] Furthermore, the activation energy calculation results are as follows: Figure 10 As shown, the activation energy of MgH2 / TiO2-DL is 116.3 kJ / mol. -1 ;

[0103] Compared with Example 1, it can be seen that adding TiO2-DL with low defect content can also significantly reduce the hydrogen desorption activation energy of MgH2.

[0104] To further demonstrate the impact of oxygen vacancy level and bipolar hydrogen content on hydrogen storage performance, a temperature-programmed hydrogen release performance test was conducted. The test results are as follows: Figure 9 As shown, the initial hydrogen release temperature of MgH2 / TiO2-DL is 230.7℃, the complete hydrogen release temperature is 350℃, the complete hydrogen release amount is 6.64 wt.%, and the hydrogen release rate is 97.1%.

[0105] Compared with Example 1, it can be seen that the introduction of a catalyst with low defect degree and bipolar hydrogen content can significantly reduce the initial hydrogen release temperature and the complete hydrogen release temperature of MgH2, and improve the hydrogen release rate.

[0106] Example 3

[0107] A method for preparing a magnesium-based composite hydrogen storage material based on a high oxygen defect structure and high bipolar hydrogen TiO2 is disclosed. Unless otherwise specified, the steps are the same as in Example 1, except that in step 2, the amount of NaBH4 reducing agent is increased to increase the oxygen defect content. Specifically, the mass ratio of TiO2 precursor to NaBH4 reducing agent is 1:1. The high oxygen defect structure and high bipolar hydrogen TiO2 obtained in step 2 is referred to as TiO2-DH. Furthermore, the magnesium-based composite hydrogen storage material based on a high oxygen defect structure and high bipolar hydrogen TiO2 obtained in step 3 is referred to as MgH2 / TiO2-DH.

[0108] To quantitatively analyze the defect content, i.e., oxygen vacancies, of TiO2-DH, TG testing was conducted under air conditions. The test results showed that the oxygen uptake of TiO2-DH was 11.1%. Calculations indicated that the specific O content was 1.5%, therefore, the chemical formula is represented as TiO2-DH. 1.5 -DH.

[0109] To further quantify the content of bipolar hydrogen in TiO2-DH, an isothermal hydrogen absorption test was conducted. The hydrogen absorption capacity of TiO2-DH was 0.8 wt.%, from which the specific content of bipolar hydrogen was determined to be 0.58.

[0110] To further prove the H in bipolar hydrogen + and H − The ratio was used for NMR testing, H + and H − The ratio is 6:4. Based on the results of the isothermal hydrogen absorption test, the value of positively charged hydrogen in the bipolar hydrogen is 0.35, and the value of negatively charged hydrogen is 0.23. Therefore, the chemical formula is represented as TiO₂. 1.5 (H + ) 0.35 (H − ) 0.23 .

[0111] The above tests show that Example 3 successfully prepared a high oxygen defect structure and a high bipolar hydrogen TiO2.

[0112] To demonstrate the hydrogen storage performance of MgH2 / TiO2-DH, kinetic performance tests were conducted.

[0113] The test results at a hydrogen release temperature of 300℃ are as follows: Figure 7 As shown, the hydrogen release rate of MgH2 / TiO2-DH at a hydrogen release time of 7 min is 6.52 wt.%;

[0114] The test results at a hydrogen release temperature of 280℃ are as follows: Figure 8As shown, the hydrogen release rate of MgH2 / TiO2-DH at a hydrogen release time of 15 min was 5.64 wt.%.

[0115] Furthermore, the activation energy calculation results are as follows: Figure 10 As shown, the activation energy of MgH2 / TiO2-DH is 99.7 kJ / mol. -1 ;

[0116] Compared with Example 1, it can be seen that adding TiO2-DH with high defect content can significantly reduce the hydrogen desorption activation energy of MgH2.

[0117] To further demonstrate the hydrogen storage performance of MgH2 / TiO2-DH, a temperature-programmed hydrogen release performance test was conducted.

[0118] Test results are as follows Figure 9 As shown, the initial hydrogen release temperature of MgH2 / TiO2-DH is 209.5℃, the complete hydrogen release temperature is 315℃, the complete hydrogen release amount is 6.67 wt.%, and the hydrogen release rate is 97.5%.

[0119] Compared with Example 1, it can be seen that the introduction of high defect structure and high bipolar hydrogen TiO2 can significantly reduce the initial hydrogen desorption temperature and the complete hydrogen desorption temperature of MgH2, and improve the hydrogen desorption rate.

[0120] Examples 1, 2, and 3 demonstrate that the addition of a TiO2 catalyst with oxygen defects and bipolar hydrogen can significantly improve the hydrogen storage kinetics of MgH2.

[0121] The above embodiments and comparative examples demonstrate that TiO₂ with defective structures... x (H + ) y (H − ) z / MgH2 exhibits superior hydrogen storage kinetics because its structure contains both positively valent hydrogen (H) atoms. + With negatively charged hydrogen H − That is, a bipolar hydrogen structure is formed, in which H + With H in MgH2 − The electrostatic attraction between them helps to weaken the Mg-H bond and promotes the dissociation and diffusion of hydrogen atoms on the MgH2 surface. Therefore, it can significantly promote the diffusion and desorption of hydrogen from the MgH2 lattice, and has a clear advantage in reducing the hydrogen desorption energy barrier.

Claims

1. A TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties, characterized in that: It is prepared by ball milling TiO2-D and MgH2, wherein MgH2 is the matrix material and TiO2-D is the catalyst; the TiO2-D is prepared by chemical reduction method, and TiO2 and TiO2-D have anatase structure; in the TiO2-D, the content of positive hydrogen in the bipolar hydrogen ranges from 0 to 0.35, and the content of negative hydrogen ranges from 0 to 0.

23.

2. A method for preparing a TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties, characterized in that... Includes the following steps: Step 1, Preparation of TiO2 precursor: First, at room temperature, tetrabutyl titanate, concentrated hydrochloric acid and anhydrous ethanol are stirred and thoroughly dissolved to obtain a uniform and transparent sol. Then, the sol is dried. Finally, the sol is calcined in air at a certain temperature to obtain TiO2 precursor. Step 2, preparation of TiO2 with bipolar hydrogen characteristics: First, under an argon atmosphere, the TiO2 precursor obtained in Step 1 is ball-milled and mixed with NaBH4 reducing agent. Then, it is heat-treated. Finally, the heat-treated solid powder is placed in hydrochloric acid solution and magnetically stirred. After stirring, it is washed, centrifuged and vacuum dried to obtain TiO2 with bipolar hydrogen characteristics, abbreviated as TiO2-D. Step 3, Preparation of MgH2 / TiO2-D: Under an argon atmosphere, MgH2 and TiO2-D obtained in Step 2 are ball-milled to obtain a TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties, abbreviated as MgH2 / TiO2-D.

3. The preparation method according to claim 2, characterized in that: In step 1, the mixing ratio of tetrabutyl titanate, concentrated hydrochloric acid and anhydrous ethanol is 72:2:15, and the stirring time is 12-24 h. In step 1, the drying temperature is 60-80℃ and the drying time is 12-24 h; In step 1, the calcination temperature is 450℃ and the calcination time is 2 h.

4. The preparation method according to claim 2, characterized in that: In step 2, the mass ratio of TiO2 precursor to NaBH4 is 2:1; In step 2, the ball milling conditions are as follows: under argon gas, the ball-to-material ratio is 20:1, the ball milling speed is 150 rpm, and the ball milling method is intermittent ball milling, specifically, the ball milling time is 10 min, the pause time is 10 min, and then the ball milling is reversed, with a total ball milling time of 2 h. In step 2, the heat treatment conditions are as follows: under argon atmosphere, the gas flow rate is 150 mL / min. -1 The heat treatment temperature was 450℃ and the heat treatment time was 2 hours. In step 2, the concentration of hydrochloric acid is 1 mol L. -1 The amount of hydrochloric acid is 100 mL, and the stirring conditions are: stirring speed of 600-800 rpm and stirring time of 12-24 h.

5. The preparation method according to claim 2, characterized in that: In step 3, the mass ratio of MgH2 to TiO2-D obtained in step 2 is 9:1; In step 3, the ball milling conditions are as follows: under argon gas, the ball-to-material ratio is 20:1, the ball milling speed is 300 rpm, and the ball milling method is intermittent ball milling, specifically, the ball milling time is 10 min, the pause time is 10 min, and then the ball milling is reversed, with a total ball milling time of 20 h.

6. A TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties, characterized in that: At a hydrogen release temperature of 300℃ and a hydrogen release pressure of 0.001 MPa, the hydrogen release amount of MgH2 / TiO2-D reached 6.20-6.41 wt.% after a hydrogen release time of 7 min; at a hydrogen release temperature of 280℃ and a hydrogen release pressure of 0.001 MPa, the hydrogen release amount of MgH2 / TiO2-D reached 5.81-5.98 wt.% after a hydrogen release time of 15 min; the activation energy of MgH2 / TiO2-D was 92-116 kJ / mol. -1 .

7. A TiO2 magnesium-based composite hydrogen storage material with bipolar hydrogen properties, characterized in that: Under vacuum conditions, the heating rate is 2℃ min. -1 When the temperature rises from room temperature to 450℃, the initial hydrogen release temperature of MgH2 / TiO2-D is 201.3-205.8℃, the complete hydrogen release temperature is 345-350℃, and the complete hydrogen release amount is 6.52-6.64 wt.%.